2003
DOI: 10.1364/oe.11.002970
|View full text |Cite
|
Sign up to set email alerts
|

A largely tunable CFBG-based dispersion compensator with fixed center wavelength

Abstract: A largely tunable chirped fiber Bragg grating (CFBG)-based dispersion compensator with fixed center wavelength is demonstrated. Tunable dispersion ranging from 178 to 2126 ps/nm, corresponding to a large range of 3-db bandwidth from 0.42 to 5.04 nm, is realized by using a 10 cm-long CFBG with an original bandwidth of 1.61 nm. The variation in center wavelength is less than 0.2 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…Despite extensive theoretical and simulation studies on the AST approach including this work, quite little experimental study on this topic has been reported so far, mainly due to the lack of good optical filter offering an engineered group delay or dispersion profile. Potential good candidates to achieve the particularly designed AST filter include customized fibre Bragg gratings [14,22,23], chromo-modal dispersion mechanism [24] with the aid of mode-selective excitation [25], and photonic crystal fibre (PCF) with precisely controlled chromatic dispersion profile [26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive theoretical and simulation studies on the AST approach including this work, quite little experimental study on this topic has been reported so far, mainly due to the lack of good optical filter offering an engineered group delay or dispersion profile. Potential good candidates to achieve the particularly designed AST filter include customized fibre Bragg gratings [14,22,23], chromo-modal dispersion mechanism [24] with the aid of mode-selective excitation [25], and photonic crystal fibre (PCF) with precisely controlled chromatic dispersion profile [26].…”
Section: Discussionmentioning
confidence: 99%
“…FBGs used as wavelength-selective channel dropping or inserting filters [3] must have very narrow spectral widths, whereas when used for dispersion compensation [4], broadband FBGs are required. The background loss can be detrimental, thus decreasing the reflectivity saturation value at the Bragg wavelength, increasing the out-of-band transmission loss, and broadening the reflectivity spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…1) can be analyzed in a number of ways [1,2], among which is the finite-element method, the method of auxiliary sources, the method of moments (MoM), and so forth. The MoM can be employed in both spectral [3] and spatial [4] domains. Both solutions work well if the cylinder is electrically small, that is, r 0 / 0 Ͻ 1, where r 0 is the radius of the dielectric substrate (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations